K/BxN Serum-Transfer Arthritis as a Model for Human Inflammatory Arthritis - Christensen, Anne D.; Haase, Claus; Cook, Andrew D.; Hamilton, John A. (Frontiers in Immunology, 2016)
The K/BxN serum-transfer arthritis (STA) model is a murine model in which the immunological mechanisms occurring in rheumatoid arthritis (RA) and other arthritides can be studied. To induce K/BxN STA, serum from arthritic transgenic K/BxN mice is transferred to naive mice and manifestations of arthritis occur a few days later. The inflammatory response in the model is driven by autoantibodies against the ubiquitously expressed self-antigen, glucose-6-phosphate isomerase (G6PI), leading to the formation of immune complexes that drive the activation of different innate immune cells such as neutrophils, macrophages and possibly mast cells. The pathogenesis further involves a range of immune mediators including cytokines, chemokines, complement factors, Toll-like receptors, Fc receptors, and integrins, as well as factors involved in pain and bone erosion. Hence, even though the K/BxN STA model mimics only the effector phase of RA, it still involves a wide range of relevant disease mediators. Additionally, as a murine model for arthritis, the K/BxN STA model has some obvious advantages. Firstly, it has a rapid and robust onset of arthritis with 100% incidence in genetically identical animals. Secondly, it can be induced in a wide range of strain backgrounds and can therefore also be induced in gene-deficient strains to study the specific importance of disease mediators. Even though G6PI might not be an essential autoantigen, for example, in RA, the K/BxN STA model is a useful tool to understand how autoantibodies in general drive the progression of arthritis by interacting with downstream components of the innate immune system. Finally, the model has also proven useful as a model wherein arthritic pain can be studied. Taken together, these features make the K/BxN STA model a relevant one for RA and it is a potentially valuable tool especially for the pre-clinical screening of new therapeutic targets for RA and perhaps other forms of inflammatory arthritis. Here we describe the molecular and cellular pathways in the development of K/BxN STA focusing on the recent advances in the understanding of the important mechanisms. Additionally, this review provides a comparison of the K/BxN STA model to some other arthritis models.